How do you differentiate y=e^(ktansqrtx)y=ektan√x? Calculus Basic Differentiation Rules Chain Rule 1 Answer mozzie May 23, 2017 Derivative = k/2 x^(-1/2) sec^2(sqrtx)e^(ktan(sqrtx)k2x−12sec2(√x)ektan(√x) Explanation: If f(x) = e^(g(x))f(x)=eg(x) then f'(x) = g'(x)e^(g(x)) Answer link Related questions What is the Chain Rule for derivatives? How do you find the derivative of y= 6cos(x^2) ? How do you find the derivative of y=6 cos(x^3+3) ? How do you find the derivative of y=e^(x^2) ? How do you find the derivative of y=ln(sin(x)) ? How do you find the derivative of y=ln(e^x+3) ? How do you find the derivative of y=tan(5x) ? How do you find the derivative of y= (4x-x^2)^10 ? How do you find the derivative of y= (x^2+3x+5)^(1/4) ? How do you find the derivative of y= ((1+x)/(1-x))^3 ? See all questions in Chain Rule Impact of this question 1736 views around the world You can reuse this answer Creative Commons License